Ngā Puna Aroha: towards an indigenous-centred freshwater allocation framework for Aotearoa New Zealand. Issue 1 (2nd January 2021) - Taylor, Lara Bernadette; Fenemor, Andrew; Mihinui, Roku; Sayers, Te Atarangi; Porou, Tina; Hikuroa, Dan; Harcourt, Nichola; White, Paul; O'Connor, Martin
ABSTRACT: Aotearoa New Zealand's environmental policy and legislation recognises Māori Indigenous principles and values, and gives prominence to Te Mana o te Wai (the authority of water itself). However, current policy, legislation, and practice are inadequate for enabling Māori rights and interests in water takes and instream flows and levels, in terms of both involvement and specific allocation mechanisms supporting Māori values. We argue that a policy and implementation space needs to be created that ensures indigenous Māori engagement and outcomes in freshwater governance, planning, and management. This space should provide for an integrated, precautionary, and bicultural 'First Principles' approach, ensuring that Māori rights and interests consistent with Te Tiriti o Waitangi/the Treaty of Waitangi (1840) are enabled, including the exercise of mātauranga Māori (knowledge informed by Māori worldviews), tikanga (Māori customs and lore), and kaitiakitanga (guardianship). We outline a potential water allocation framework, Ngā Puna Aroha, that could provide direction and give confidence and certainty to the implementers of national water policy. Such an approach would need to be supported by a broader bicultural policy and we suggest an overarching philosophy Ngā Taonga Tuku Iho, which would encompass all natural 'resource' management, providing a korowai (cloak) for the management of each particular 'resource' or taonga (treasure) including freshwater. This type of bicultural proposal could inform freshwater and wider natural 'resource' management policymaking, regulatory frameworks, and implementation nationally and internationally.